Divine multiplicity trinities, diversities, and the nature of relation - Boesel, Chris; Ariarajah, S. Wesley (Transdisciplinary theological colloquia, 2014)
"The essays in this volume pose critical questions and suggest constructive possibilities regarding the extent to which trinitarian and pluralist discourses can be put into fruitful conversation with one another. On one hand, the volume interrogates the possibilities of trinitarian theology and its ethical promise with regard to divine and creaturely relationality by putting it into specific engagement with discourses of pluralism, diversity, and multiplicity. It asks how trinitarian conceptions of divine multiplicity might open the Christian tradition to increasingly more creative and affirming visions of creaturely identities, difference, and relationality--including the specific difference of religious plurality. Alternatively, where can the triadic patterning evident in the Christian theological tradition be seen to have always exceeded the boundaries of Christian thought and experience, inhabiting and determining other religious traditions' conceptions of divine and/or creaturely reality in ways internal to their own distinctive histories? On the other hand, the volume interrogates the possibilities of various discourses on pluralism by putting them in a very particular and concrete pluralist context. Religious pluralists, comparative theologians, and scholars of religious studies are place alongside and put into conversation with theological and doctrinal work carried out within the (albeit broadly conceived) normative thread of the Christian trinitarian tradition. To what extent can pluralist discourse collect within itself a convergent diversity of orthodox, heterodox, postcolonial, process, poststructuralist, liberationist, and feminist sensibilities while avoiding irruptions of conflict, competition, or the logic of mutual exclusion? The goal of this collection is that, in the midst of these crisscrossing lines of cohering and/or conflictual difference about the theme of divine multiplicity, critical and imaginative visions of divine and creaturely relations might be generated that can inform future theological, philosophical and ethical work in transdisciplary, inter-religious and intra-religious contexts"--